Factors that influence customers' preferences to choose Islamic pawn broking in rural area / Muhammad Nazirul Syafiq Ithnin - Ithnin, Muhammad Nazirul Syafiq (Faculty of Business Management, 2018)
Besides the function played by the formal financial institution, there also has an important function that played by the informal financial institution through their endeavour in providing credit facilities to the society. The informal financial institution such a pawnshop has increased over the past few years, especially during the rugged economic climate. In our country, the pawn broking business has provided promptly service to the people in need for the cash in various form. Primarily, our country has two approaches of pawn broking which are conventional pawn broking and Islamic pawn broking. Given from that, the aim of this study is to explore and examines the theoretical frameworks of factors that influence customers' preferences to choose Islamic pawn broking in rural area using descriptive analysis of the factors accepting Islamic pawn broking. Five factors are Shariah View, Pledge Assets, and Customer Service, Advertisement and one new variables that was created which is Social Factors. This research was conducted using a quantitative methods. 150 of the questionnaires were distributed personally. Data analysis was run in SPSS in order to determine which factors that influence customers' preferences to choose Islamic pawn broking in rural area. Lastly, this study has turned out the strong element that positively significant toward customer preferences to choose Islamic pawn broking scheme which are Shariah view and Social factors.